Bruce Songs : The Music of Bruce Springsteen, Album-By-Album, Song-by-Song. - Womack, Kenneth; Campbell, Kenneth L. (New Brunswick : Rutgers University Press, 2024)
Bruce Songs: The Music of Bruce Springsteen, Album-by-Album, Song-by-Song is an authoritative guide coauthored by renowned music scholar Kenneth Womack and music historian Kenneth L. Campbell and offering an in-depth exploration of Bruce Springsteen's musical legacy. Covering Springsteen's entire discography, from Greetings from Asbury Park, N.J. to Only the Strong Survive, this unique book combines historical context, literary analysis, and meticulous research. Unlike any other resource, it provides detailed analyses of each album, essays on their historical significance, and a chronological examination of every studio song. Discover the stories behind the recordings and gain insight into Springsteen's creative process. Rich with contemporary reviews, insider accounts, photographs, and special sections highlighting pivotal moments and key figures, Bruce Songs is an indispensable companion for fans and scholars. It offers an immersive journey through the music of The Boss, making it an essential read for anyone captivated by Springsteen's enduring musical legacy.
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- The Studio Albums -- Discography -- Bibliography and Sources for Further Reading -- Acknowledgments -- Index of Songs -- About the Authors
Description based upon print version of record.
JSTOR
Keywords: Springsteen, Bruce -- Criticism and interpretation; Springsteen, Bruce -- Analysis, appreciation; Springsteen, Bruce -- Discography; Rock music -- United States -- History and criticism; Rock (Musique) -- États-Unis -- Histoire et critique; MUSIC / General; Electronic books